(untitled) (Research, Society and Development, 2022)
The Rural Environmental Registry (RER) consists of an electronic record of information on rural properties that aims to integrate environmental information on properties, in order to contribute to the creation of a strategic database, used to control, monitor and combat deforestation, helping the process of environmental regularization of rural properties. The objective was to carry out an environmental diagnosis in the state of Minas Gerais, through the information available on the website of the National Rural Environmental Registry System (NRERS). 85 municipalities were selected, comprising 10% of the total municipalities that make up the state. Geostatistical analysis was used to generate maps. The data provided by NRERS presented itself as an important tool for environmental control and regularization. Through the information obtained, it is possible to analyze the Permanent Preservation Areas and Legal Reserve, in addition to allowing for comparing the agricultural zoning with the productive characteristics of each region of the state.